Solid And Liquid Pineapple Waste Utilization For Lactic Acid Fermentation - Abdullah Abdullah (Dept. of Chemical Engineering, Diponegoro University, 2007)
The liquid and solid pineapple waste contain mainly sucrose, glucose,fructose, and other nutrients. It therefore can potentially be used as carbon source for fermentation to produce organic acid. Recently, lactic acid has been considered to be an important raw material for production of biodegradable lactate polymer, the experiments were carried out in batch fermentation using the liquid and solid pineapple waste to produce lactic acid. The anaerobic fermentation of lactic acis were performed at 40 0C, ph 6, 5% inocolum, and 50 rpm. Initially results show that the liquid pineapple waste by using Lactobacillus delbrueckii can be used as carbon source for lactic acid fermentation. The production of lactic acid are found to be 79% yield, while only 56% yield was produced y using solid waste.Keywords : Lactic acid fermentation, Pineapple waste, Lactobacillus delbrueckii